PENGARUH KARAKTERISTIK UMKM TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN SELF EFFICACY SEBAGAI PEMODERASI - Ausgaria Ega; Sari Rahmadhani (JURNAL LENTERA BISNIS, 2024)
This study aims to understand the factors that affect the quality of loan proceeds for students who use self-efficacy as a moderating model. The data collection technique uses a quantitative survey method that is derived from providing a silent and timely questionnaire to 117 respondents who are students at UMKM Nasabah BTPN Syariah, with the results being analyzed using a Likert scale. Based on data analysis using the regression analysis technique with interaction, alat uji PROCESS SPSS 27. It appears that the trade owner's discernment, the employees' recognition, and the business's life span positively affect the quality of the SAK EMKM credit portfolio. Then again, accounting information negatively affects the quality of SAK EMKM's money exchanges. The relationship between the owner's, operator's, and long-term commerce recognitions and the quality of the business's budgetary portfolio is not influenced by self-efficacy. Self-efficacy adjusts the relationship between mindfulness and mindfulness.